Talking About (My) Generation: The Use of Generation as Rhetorical History in Family Business. (March 2023) - Lubinski, Christina; Gartner, William B.
The concept of "generation" in family business scholarship is primarily used genealogically to reflect family lineage. This approach fails to account for complementary perspectives that are more established in history: "generation" as a category of societal belonging and a form of rhetorical history. Using a constitutive history approach, we identify four usages of "generation" by which these narratives can establish continuity or change in how families talk about themselves and foreground either family dynamics or embeddedness in societal developments. The form of historical narratives and how they mark time, we argue, is core to understanding rhetorical history processes.